Keanekaragaman Jenis EPT (Ephemeroptera, Plecoptera, Trichoptera) sebagai Indikator Kesehatan Sungai Opak, Daerah Istimewa Yogyakarta - Saleh, Yogi Faturahman; Suwadji, Siman; Yuslinawari (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2025)
Macroinvertebrates from the EPT group (Ephemeroptera, Plecoptera, and Trichoptera) are known as sensitive bioindicators of aquatic pollution. This study aims to assess the ecological health of the Opak River in the Special Region of Yogyakarta using biomonitoring based on the presence and diversity of EPT taxa. Sampling was conducted at three observation sites—upstream (Leses Village), midstream (Bawuran), and downstream (Sriharjo)—using kick sampling and jabbing methods. The results showed that EPT were only found at the upstream station, represented by two families (Psychomyiidae and Polycentropodidae), while no EPT were detected at the midstream and downstream stations. Based on the Biotilik index and supporting parameters, the water quality in the upstream area was classified as moderately polluted, whereas the midstream and downstream areas were classified as heavily polluted. The decline in river quality correlates strongly with anthropogenic activities such as agriculture, livestock farming, industrial waste, and household sewage discharge. This study emphasizes the importance of river conservation and management through biological indicators to support the sustainability of freshwater ecosystems.